Protective effects of silver nanoparticles in isoproterenol-induced myocardial infarction in rats - Arozal, Wawaimuli; Monayo, Edwina Rogayah; Barinda, Agian Jeffilano; Perkasa, Dian Pribadi; Soetikno, Vivian; Nafrialdi, Nafrialdi; Louisa, Melva (Frontiers in Medicine, 2022)
Background Silver nanoparticles (AgNPs) are widely used in the medical field, including cardiovascular. However, limited research has investigated the effect of AgNPs on the protection of myocardial infarction (MI). Objectives Isoproterenol (Iso)-induced MI and the cardiac protection offered by AgNPs were investigated in the present study. Additionally, we characterized the profile of Ag in the form of nanoparticles. Methods Twenty-four male Wistar rats were randomly divided into four groups as follows: normal, Iso, Iso + AgNO3, and Iso + AgNP groups. AgNPs and silver ion (AgNO3) were administered intraperitoneally at 2.5 mg/kg BW for 14 days. Iso induction was performed using two doses of 85 mg/kg BW given subcutaneously on days 13 and 14. Blood and cardiac tissue samples were taken 24 h after the last dose of Iso and checked for Creatine Kinase-MB (CK-MB), lactate dehydrogenase in plasma along with oxidative stress parameters, mitochondria biogenesis markers, and inflammation representative genes in cardiac tissue. Additionally, we analyzed the histopathological features in cardiac tissue. Results The silver was confirmed in the form of nanoparticles by its size at intervals of 8.72–37.84 nm. Both AgNO3 and AgNPs showed similar cardioprotective effects, as shown by the decrease in biochemical markers of cardiac toxicity, namely, CK-MB. Additionally, AgNPs group have better efficacy compared with AgNO3 group in ameliorating Iso-mediated oxidative stress production, as evidenced by the significant decrease in malondialdehyde level and increased superoxide dismutase activity (P < 0.0001 and P < 0.01, respectively) in cardiac tissue compared with the Iso group. Mechanistically, AgNPs, but not AgNO3, enhanced the expression levels of mitochondrial transcription factor A and peroxisome proliferator-activated receptor-gamma coactivator 1-alpha in post-MI heart and reduced the protein expression of nuclear factor-kappa B (NF-κB) assessed by western blot analysis. Furthermore, these results were confirmed with the histopathological evaluation of cardiac tissue. Nevertheless, pretreatment with either AgNO3 or AgNPs improved the aspartate aminotransferase level. Conclusion These results suggested that AgNPs have more superior cardioprotective effect compared with AgNO3 against Iso-induced MI, at least in part through amelioration of NF-κB expression level induced by oxidative stress overproduction.